Comparison of 3 T and 1.5 T for T2* magnetic resonance of tissue iron. Issue 1 (December 2016) - Alam, Mohammed; Auger, Dominique; McGill, Laura-Ann; Smith, Gillian; He, Taigang; Izgi, Cemil; Baksi, A.; Wage, Rick; Drivas, Peter; Firmin, David; Pennell, Dudley
Abstract Background T2* magnetic resonance of tissue iron concentration has improved the outcome of transfusion dependant anaemia patients. Clinical evaluation is performed at 1.5 T but scanners operating at 3 T are increasing in numbers. There is a paucity of data on the relative merits of iron quantification at 3 T vs 1.5 T. Methods A total of 104 transfusion dependent anaemia patients and 20 normal volunteers were prospectively recruited to undergo cardiac and liver T2* assessment at both 1.5 T and 3 T. Intra-observer, inter-observer and inter-study reproducibility analysis were performed on 20 randomly selected patients for cardiac and liver T2*. Results Association between heart and liver T2* at 1.5 T and 3 T was non-linear with good fit (R 2  = 0.954, p  < 0.001 for heart white-blood (WB) imaging;R 2  = 0.931, p  < 0.001 for heart black-blood (BB) imaging;R 2  = 0.993, p  < 0.001 for liver imaging). R2* approximately doubled between 1.5 T and 3 T with linear fits for both heart and liver (94, 94 and 105 % respectively). Coefficients of variation for intra- and inter-observer reproducibility, as well as inter-study reproducibility trended to be less good at 3 T (3.5 to 6.5 %) than at 1.5 T (1.4 to 5.7 %) for both heart and liver T2*. Artefact scores for the heart were significantly worse with the 3 T BB sequence (median 4, IQR 2–5) compared with the 1.5 T BB sequence (4 [3–5], p  = 0.007). Conclusion Heart and liver T2* and R2* at 3 T show close association with 1.5 T values, but there were more artefacts at 3 T and trends to lower reproducibility causing difficulty in quantifying low T2* values with high tissue iron. Therefore T2* imaging at 1.5 T remains the gold standard for clinical practice. However, in centres where only 3 T is available, equivalent values at 1.5 T may be approximated by halving the 3 T tissue R2* with subsequent conversion to T2*.